Essential oils in pandan leaves (Pandanus amaryllifolius) and curry leaves (Murraya koenigii) / Jerry Luhat Wan - Luhat Wan, Jerry (Faculty of Applied Sciences, 2009)
The composition of the essential oils extracted by hydrodistillation from leaves parts of pandan (Pandanus amaryllifolius) and curry (Murraya koenigii) were analyzed by using gas chromatography-mass spectrometry (GC-MS). The major components in Pandanus amaryllifolius was 2-acetyl-1-pyrroline but in present study only the minor component was obtained which were cycloheptasiloxane and cyclohexasiloxane. The major components in Murraya koenigii based on the previous study have been done were α-pinene.Similar to Pandanus amaryllifolius, only the minor component were obtained where it was cyclohexanone. One of the major component was obtained (3,4-octadiene) but have a very low percentage area. The yields of oil for Pandanus amaryllifolius, and Murraya koenigii were 3.76% and 4.69% respectively.